Plant diversity and ecosystem health assessment of Sanyang wetland in Wenzhou, Zhejiang - WU Qing-ling; XIA Xiao-lan; YE Jing; JIANG Lei; MIU Ke-pai; DING Bing-yang (浙江大学学报. 农业与生命科学版)
The composition and diversity characters of the vascular plant species were investigated and identified in Sanyang wetland of Wenzhou, Zhejiang. The eco-health of Sanyang wetland was assessed by comparing with Xixi wetland in Hangzhou and Jinghu wetland in Shaoxing, Zhejiang. Result showed that: 1) there were 259 kinds of vascular plants in Wenzhou Sanyang wetland, belonging to 187 genera and 73 families; 2) there were 66 wetland specialist species, including 2 submerged species, 3 fluitante species, 3 floating-leaves rooted species, 25 emerged species and 33 hygrophyte species; 3) there were 4 species included in state protected plant list, 1 species of suggesting to be protected and 28 exotic invasive plant species; 4) comparing with Xixi wetland and Jinghu wetland, the ratio of the aquatic species, especially submersed plants relative to total plant species, the species richness and the number of the state protected species of this wetland were low, while the number of the exotic invasive plant species were relatively high, which showed that the eco-health of Sanyang wetland was worst; 5) the results above indicated that the habitat for subsistence of wetland plant species in Sanyang wetland was destroyed by serious water pollution, and the ecological system was fragile, which needed to be protected and repaired.